In vitro Degradation of Antimicrobials during Use of Broth Microdilution Method Can Increase the Measured Minimal Inhibitory and Minimal Bactericidal Concentrations - Lallemand, Elodie A.; Lacroix, Marlène Z.; Toutain, Pierre-Louis; Boullier, Séverine; Ferran, Aude A.; Bousquet-Melou, Alain (Frontiers in Microbiology, 2016)
The antibacterial activity of some antimicrobials may be under-estimated during in vitro microbiological susceptibility tests, due to their instability under such conditions. The in vitro degradation of seven widely used antimicrobials (amoxicillin, cephalexin monohydrate, cefotaxime sodium salt, ciprofloxacin, erythromycin hydrate, clarithromycin and doxycycline hyclate) and its effect on MIC and MBC determinations was studied using the broth microdilution method, considered as the gold standard for MIC determinations. In vitro concentrations of antimicrobials, over a 24h incubation period in the medium tested without bacteria, decreased from 33% for ciprofloxacin to 69% for clarithromycin. For cephalexin, cefotaxime, clarithromycin and doxycycline which were the most degraded drugs, MIC and MBC values for one strain of E. coli and one strain of S. aureus were compared using the standard method or after ad hoc drug complementation aiming at maintaining constant drug concentration. Abiotic degradation during the standard method was associated with a significant increase of the MIC (2 antibiotics) and MBC (3 antibiotics). However, the observed discrepancy (less than one twofold dilution), even for the most degraded drug for which the concentration at 24h was reduced by two thirds, suggests that this would only be clinically significant in special cases such as slow-growing bacteria.